Occupational Sex Segregation in Agriculture : Evidence on Gender Norms and Socio-Emotional Skills in Nigeria - Das, Smita; Delavallade, Clara; Fashogbon, Ayodele; Ogunleye, Wale; Papineni, Sreelakshmi (World Bank, Washington, DC, 2021)
Occupational sex segregation is a key driver of the gender gap in earnings. Using data from 11,691 aspiring agribusiness entrepreneurs across five states in Nigeria, this paper explores the gender gap in the sectoral choice decision, and especially the role played by norms around gender roles. When given a choice of 11 agricultural value chains in a government program, the majority (54 percent) of the entrepreneurs chose to enter into poultry, a value chain with relatively lower profit potential, and women were more likely to choose poultry than men. This paper finds evidence of more restrictive gender norms in Northern States, which lowers women’s likelihood of crossing over to potentially more lucrative value chains. The gender gap in sectoral choice is also attributed to differences in work experience especially in agricultural activities and in the chosen value chain, as well as in land ownership and differential access to tertiary-level education. The paper shows that women with more experience in male-dominated value chains exhibit lower self-efficacy, which could reflect the challenges they face when deviating from social norms to operate within these sectors.